Serbia on the road to EU accession : consequences for agricultural policy and the agri-food chain - Berkum, S. van (CABI, 2012)
This book aims at providing relevant background information in the event that a decision is made by the EU to begin accession negotiations with Serbia. If this happens, then the full set of Copenhagen criteria will become relevant. The book focuses on one of the Copenhagen criteria: the existence of a functioning market economy, including the existence of institutions required to support such a market economy within the EU. The book focuses on this aspect of the Copenhagen criteria in relation to agriculture, food, rural development and structural policy. The book has 11 chapters and a subject index.